Going equipped. Criminology, situational crime prevention and the resourceful offender - Ekblom, Paul (The British journal of criminology, 2000)
In showing more interest in the crime event than the offender, situational crime prevention has tended to be at the margins of mainstream academic criminology. Yet offenders can only exploit potential crime opportunities if they have the resources to take advantage of them. To understand how crime patterns are generated, situational crime prevention must also consider offender resources and their distribution and social-technical change. Resources have been central to much traditional offender-centred criminology but mainly for understanding what motivates offending. Consideration of crime-resource needs, availability, development, distribution and change provides a potential bridge between traditional offender-centred criminology and situational crime prevention